The incidence of calf morbidity and mortality due to vector-borne infections in smallholder dairy farms in Kwale District, Kenya - Muraguri, G.R.; McLeod, A.; McDermott, John J.; Taylor, N. (Elsevier, 2005)
An observational longitudinal study was carried out on 92 randomly selected smallholder farms in two coastal lowland zones of Kwale District in Kenya between December 1997 and November 1999. The objective was to estimate the incidence of the main vector-transmitted diseases in pre-weaned calves. From an initial 41 pure or cross-bred Bos taurus calves which were less than 2 months and whose birth and disease histories were known, study calves were recruited progressively and monitored until they were weaned at around 146 days. Overall, 130 calves in 67 farms were monitored and these contributed a total risk period of 30,062 days. Disease parameters were analysed and compared as true annual and age-specific incidence rates. The incidences of East Coast fever (ECF) (23.1%) and trypanosomosis (29.1%) were the highest among the vector-borne diseases. The corresponding mortality incidence rates of ECF and trypanosomosis were 10.9 and 3.6%, respectively. The annual incidence rates of anaplasmosis and babesiosis were 10.9 and 1.2%, respectively. There was no mortality arising specifically from anaplasmosis or babesiosis. Analysis of survival times to natural infection indicated that the field challenge resulting to cases of trypanosomosis was much higher compared to the risk of either ECF or anaplasmosis. It was concluded that these vector-borne diseases constrain production of replacement stock in this coastal lowlands region of Kenya.